Hungarian Monitoring, 21 February 1990 . [Magyar rádiófigyelő], 1990. február 21 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - USSR: Gorbachev on the question of German unity, Soviet troop withdrawals from Czechoslovakia - America lifts economic sanctions against Czechoslovakia - German re-unification - Reports from Bucharest Domestic Affairs: - American deputy foreign minister's talks in Budapest - Elections: M. Szűrös receives opposition party leaders, election programs, press coverage - Hungary's relations with the Warsaw Pact and NATO Economy: - Hungarian Credit Bank saves Ikarusz Külpolitika: - SZU: Gorbacsov a német-egység kérdéséről, a szovjet csapatok kivonása Csehszlovákiából - Amerika feloldja a Csehszlovákia elleni gazdasági szankciója - A német egység kérdése - Bukaresti tudósítások Belpolitika: - Az amerikai külügyminiszter helyettes budapesti tárgyalásai - Választás: Szűrös M. fogadta ellenzéki pártok vezetőit, választási műsorok, sajtómegjelenés - Magyarország VSZ és NATO kapcsolata Gazdaság: - A Magyar Hitelbank megmentette az Ikaruszt